Digital Health Promotion Effectiveness on Metro City Health Office Instagram: EPIC Model Analysis - Lindasari, Eci; Putri, Dian Utama Pratiwi; Budiati, Endang; Pramudho, Kodrat; Setiaji, Bambang (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2026)
This study aims to analyze the effectiveness of digital health promotion messages delivered through the Metro City Health Office’s Instagram account using the EPIC Model framework—Empathy, Persuasion, Impact, and Communication—and to identify which EPIC dimension most strongly influences perceived message effectiveness. This study employed a quantitative, cross-sectional design. Respondents were 110 Instagram users who met predefined inclusion criteria and were selected using purposive sampling. Data were collected through an online questionnaire. Bivariate analysis showed all EPIC dimensions had positive and statistically significant correlations with message effectiveness (p < 0.05), with the strongest correlation observed for Impact. Multivariate regression revealed that EPIC dimensions simultaneously had a significant effect on message effectiveness, with R² = 0.968, indicating that the model explained 96.8% of the variance in perceived effectiveness. When tested simultaneously, only Impact remained statistically significant and emerged as the dominant predictor (standardized Beta ≈ 0.891–0.905, p = 0.000), while Empathy, Persuasion, and Communication did not show significant unique contributions in the full model. Digital health promotion through the Metro City Health Office Instagram account is perceived as effective, primarily driven by the Impact dimension.